Global Job Quality : Evidence from Wage Employment across Developing Countries - Hovhannisyan, Shoghik; Montalva-Talledo, Veronica; Remick, Tyler; Rodríguez-Castelán, Carlos; Stamm, Kersten (World Bank, Washington, DC, 2022)
Measuring job quality across countries has been challenging and has relied typically on a single indicator, such as formality or wages. To contribute to this critical policy issue, this paper presents a first global estimate of job quality departing from microdata. It assembles a harmonized global data set of labor force and household surveys to produce a measure of job quality across four dimensions: sufficient income, access to employment benefits, job stability, and adequate working conditions. The results for 40 developing countries show significant variation in job quality across countries, economic sectors, and sociodemographic characteristics, including age, location, and educational attainment. Countries in the Latin America and the Caribbean region have relatively higher levels of job quality, while countries in Sub-Saharan Africa display the lowest levels of job quality. Most workers in the sectors of finance and business services, public administration, and utilities have, on average, better jobs. Higher education matters in securing greater job quality, while the average job quality of wage employment is relatively similar between men and women but with some variation in income and working conditions.